Weaving Textiles: Textile Consumption for Travel and Warfare - Eva Andersson Strand (Norsk arkeologisk selskap, 2021)
Textile research has demonstrated that new types of textiles were introduced to Scandinavia in the latter part of the Scandinavian Iron Age (AD 700–900). The archaeology of the period displays an increased number of textile tools, and large concentrations of pit houses dedicated to textile production. This era also saw the introduction of sails to Scandinavia, which is one of the obvious reasons for textiles and textile production becoming such an important part of Viking Age society. However, hitherto the value of the textiles has mostly been ignored, and its impact rarely discussed in research. This article will attempt to remedy this and poses important questions, such as: what was the economic value of the textiles needed for travel and warfare, and what was the value of the textiles used on a journey? In the article, the 10th century Ladby ship from Fyn in Denmark, is used to exemplify the demands and economic value of all textiles of one single ship, on one journey. I will use an interdisciplinary approach, including analyses of archaeological textiles; iconography; and early medieval texts. The aim of this novel method is to highlight the importance of textiles. It will also explore how journeys under sail and warfare contributed to the increased consumption of textiles.